STUDENTS’ PERCEPTION ON THE USE OF ENGLISH SONGS TO LEARN PRONUNCIATION - Irawan Makasoe; Nihta Liando; Paula Rombepajung (Program Studi Pendidikan Bahasa Inggris, 2022)
The aim of this research is to identify the perceptions of students about the use of English songs to learn pronunciation. The researcher used questionnaire to collect the data. The researcher used descriptive method which is survey method to analyze the data. Survey method was used to analyze the data directly from people. The population and sample of this research were the second grade students at SMA YBP Buntong Tateli. There were 20 students participated in this research. Based on the findings of the research, there are 3 indicators such as experience of using the media, learning outcomes and the effectiveness and availability of media. It was found that the students as the sample gave positive responses about the use of songs as a media of learning English especially to learn pronunciation, and the perception from the statements were dominated by agreement. The conclusion was English songs could be useful for students in the process of learning English, It could be an easy and simple media for students to learn English. It was suggested to English teachers to always be good in teaching English, and look for students interests so the learning process would be more enjoyable and make students could receive the lessons given well